Emergency Transition to Online Learning and New Opportunities for Educational Stakeholders: Review of Publications - Kuryan, Maria L.; Voronina, Elena A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2023)
The authors review the results of scientific research on the impact of the emergency transition to e-learning in higher education institutions caused by the COVID-19 pandemic. Despite a noticeable number of publications considering the disadvantages of this translation, a comprehensive analysis of the possible advantages and new opportunities associated with e-learning in an emergency has not yet been carried out. The purpose of this review is to systematize Russianand English-language empirical studies (2020-2022), addressing a number of favorable aspects of the transition to online learning. The analysis is focused on two main groups of stakeholders in the educational process: university students and university teachers. The results show that the main positive changes in student life have led to: reduced resource costs, improved quality of academic life and new opportunities for personal development. Teachers reported an increased willingness to innovate and take advantage of new opportunities for professional development and interaction. The analysis provides a holistic view of the effects of the emergency transition to e-learning in higher education. This information can be helpful for organizing a modern blended learning format, the quality of which is largely determined by the vectors inherent in the COVID-2019 pandemic. In addition, a comprehensive understanding of past experience can contribute to the development of readiness for possible future transformations of the educational format in response to new challenges.